Spirituality in students of the Women’s University of the Holy Heart - Bazán Gayoso, Elizabeth (2018)
This research presents a study on the orientation of the spirituality of students of the Women’s University of the Holy Heart. It explores on their religious training, their inderstanding of the social environment, their view on life and its future possibilities. In addition, it features the perceptions of students about themselves, their spiritual orientation and the importance of family. In short, it shows an approach to the personal world of young people aspiring to achieve their goals at  the beginning of the 21st century, marked by dazzling scientific and technological changes that belittle the significance of what is really important: the relationship with God, the encounter with oneself and others.